Understanding Online Political Participation: Theory of Planned Behavior and Social Identity Model of Deindividuation Effect To Predict Online Petition Behavior - Triwibowo, Whisnu (JURNAL KOMUNIKASI INDONESIA, 2018)
The online petition is one of the latest forms of collective action as the Internet diminishes space, time and effort constraints. This technology also enables people to exercise citizenship that can, directly and indirectly, influence the policy-making processes. Yet, it is argued the action is a shallow and passive as citizens engaged to merely clicking and thoughtless that would undermine the essence of democracy. This study examines an individual’s action in signing an electronic petition that is perceived to be a rational and volitional behavior. Furthermore, the study also identifies the type of social influence that affects individuals’ intention to participate, the social identification. To sum up, an online petition is an active behavior, which personal constructs of planned action are commingled with an external structure of collective identity that enables a person to make an adequate judgment about political engagement. For future research, interrogating message elements as a medium of persuasion will disclose the effectivity of petition to arouse social-emotional attachment to compensate face-to-face communication and non-verbal cues.